Review of the tax regime for restructuring transactions: proposed amendments - Gracia Espinar, Eduardo; Viñas Rueda, Lorena (Revista de Contabilidad y Tributación. CEF, 2010)
The object of this article is to highlight various aspects of our tax regulations that are related to restructurings which, in our opinion, should be amended in order to conform to the recent commercial regulations concerning restructurings or to EU law, or simply for technical tax reasons. The proposals for modification that we comment on do not only apply to the legal texts, but also to the criteria for interpretation maintained by the Tax Administration, being the Spanish Directorate of Taxes (Dirección General de Tributos) or the Economic Administrative Courts (Tribunales Económico-Administrativos), used in the application of the regulations which govern restructurings. We believe that the amendments that we propose are necessary, as well as desirable, since the aim of such amendments is to help businesses restructure without the tax regime curbing or obstructing its achievement, as well as to achieve legal certainty.